Risk factors for third-generation cephalosporin-resistant and extended-spectrum β-lactamase-producing Escherichia coli carriage in domestic animals of semirural parishes east of Quito, Ecuador - Siena L. Mitman; Heather K. Amato; Carlos Saraiva-Garcia; Fernanda Loayza; Liseth Salinas; Kathleen Kurowski; Rachel Marusinec; Diana Paredes; Paúl Cárdenas; Gabriel Trueba; Jay P. Graham (Public Library of Science (PLoS), 2022)
Extended-spectrum β-lactamase (ESBL)-producing and other antimicrobial resistant (AR) Escherichia coli threaten human and animal health worldwide. This study examined risk factors for domestic animal colonization with ceftriaxone-resistant (CR) and ESBL-producing E. coli in semirural parishes east of Quito, Ecuador, where small-scale food animal production is common. Survey data regarding household characteristics, animal care, and antimicrobial use were collected from 304 households over three sampling cycles, and 1195 environmental animal fecal samples were assessed for E. coli presence and antimicrobial susceptibility. Multivariable regression analyses were used to assess potential risk factors for CR and ESBL-producing E. coli carriage. Overall, CR and ESBL-producing E. coli were detected in 56% and 10% of all fecal samples, respectively. The odds of CR E. coli carriage were greater among dogs at households that lived within a 5 km radius of more than 5 commercial food animal facilities (OR 1.72, 95% CI 1.15-2.58) and lower among dogs living at households that used antimicrobials for their animal(s) based on veterinary/pharmacy recommendation (OR 0.18, 95% CI 0.04-0.96). Increased odds of canine ESBL-producing E. coli carriage were associated with recent antimicrobial use in any household animal (OR 2.69, 95% CI 1.02-7.10) and purchase of antimicrobials from pet food stores (OR 6.83, 95% CI 1.32-35.35). Food animals at households that owned more than 3 species (OR 0.64, 95% CI 0.42-0.97), that used antimicrobials for growth promotion (OR 0.41, 95% CI 0.19-0.89), and that obtained antimicrobials from pet food stores (OR 0.47, 95% CI 0.25-0.89) had decreased odds of CR E. coli carriage, while food animals at households with more than 5 people (OR 2.22, 95% CI 1.23-3.99) and located within 1 km of a commercial food animal facility (OR 2.57, 95% CI 1.08-6.12) had increased odds of ESBL-producing E. coli carriage. Together, these results highlight the complexity of antimicrobial resistance among domestic animals in this setting.